THE EFFECT OF LEARNING ENVIRONMENT, USE OF LEARNING MEDIA, AND LEARNING INDEPENDENCE ON LEARNING OUTCOMES - Aldisa, Olivea (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This research was conducted to determine how much influence the learning environment, the use ofinstructional media, and independent learning on the learning outcomes of students in class XIeconomics at SMA Negeri 35 Jakarta during distance learning (PJJ). The method used is aquantitative method with a cause and effect causality approach. The population in this studywere 106 students of class XI IPS at SMA Negeri 35 Jakarta. Determination of sample using saturatedsampling technique, data collection using survey methods. Data analysis used path analysistechniques with IBM SPSS Statistics 25. The results of this study indicate that the learning environmenthas a positive and significant effect on learning independence, the use of learning media has apositive and significant effect on learning independence, the learning environment has apositive and insignificant effect on learning outcomes, media use. learning has a positive andinsignificant effect on learning outcomes, and learning independence has a positive and significanteffect on learning outcomes. It can be concluded that learning independence cannot mediate learningenvironment variables on learning outcomes, and learning independence variables can mediate the useof learning media variables on learning outcomes.